Considering the Prospect of Utilizing Anaerobic Membrane Biofouling Layers Advantageously for the Removal of Emerging Contaminants - BouNehme Sawaya, Christelle; Harb, Moustapha (Frontiers in Chemical Engineering, 2021)
Membrane biofilm formation has traditionally been perceived as a wholly negative occurrence in membrane filtration-based wastewater treatment systems due to its resultant effect on transmembrane pressure and energy expenditure. This is the case for both membrane bioreactor (MBR) systems, generally, and anaerobic membrane bioreactors (AnMBRs), specifically. Insight gained through recent research, however, has revealed a potentially positive aspect to biofouling in AnMBR systems – namely, the improved removal of certain emerging contaminants (both microbial and chemical) from wastewater that would not otherwise be retained by the microfiltration/ultrafiltration membranes that are commonly used. Although the exact reasons behind this are not yet understood, the biofilm-specific anaerobic microbial communities that develop on membrane surfaces may play a key role in the phenomenon. Mechanisms of biofouling development in AnMBRs have recently been proven distinctly different from those that govern fouling in aerobic MBR systems. Based on these differences, it may be possible to devise operational strategies that promote the development of anaerobic biofilms on membranes while also minimizing transmembrane pressure increases. If achievable, this would serve as a sustainable basis for reducing the release of emerging contaminants such as organic micropollutants (OMPs) and antibiotic resistance genes (ARGs) with treated wastewater effluents.